Edukasi Konsep Pengembangan Halal Tourism Wisata Pantai Pengubaian dalam Meningkatkan Kepuasan Wisatawan di Kabupaten Kaur - Nabila, Naswa; B, Idwal; Pramadeka, Katra (IAI Nasional Laa Roiba Bogor, 2024)
The development of halal tourism in Indonesia has become one of the priorities to increase tourist satisfaction, especially in areas with a majority Muslim population. Pengubaian Beach has great potential to develop the concept of halal tourism. However, until now the concept has not been applied optimally. This community service program aims to provide education to tourism actors and local communities about the importance of developing halal tourism at Pengubaian Beach. The methods used include Focus Group Discussion (FGD) and socialization with the Kaur Regency Tourism Office. The results of this activity show an increase in the understanding and awareness of tourism actors, the local community towards the concept of halal tourism, with the hope of being able to increase the attractiveness of Pengubaian Beach as a sustainable tourist destination.